2016
DOI: 10.1111/ijpo.12187
|View full text |Cite
|
Sign up to set email alerts
|

The association between higher maternal pre‐pregnancy body mass index and increased birth weight, adiposity and inflammation in the newborn

Abstract: Higher maternal pre-pregnancy BMI is associated with increased newborn adiposity and inflammation. These associations may be partially mediated by maternal inflammation during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 27 publications
(36 reference statements)
2
34
0
1
Order By: Relevance
“…Our findings, that maternal BMI and excess gestational weight gain were positively associated with neonatal anthropometric measures and adiposity, are consistent with findings from other groups . The HAPO study showed that in neonates born to women with hyperglycaemia in pregnancy, excess maternal gestational weight gain was associated with increased neonatal sum of skinfolds and percentage body fat .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings, that maternal BMI and excess gestational weight gain were positively associated with neonatal anthropometric measures and adiposity, are consistent with findings from other groups . The HAPO study showed that in neonates born to women with hyperglycaemia in pregnancy, excess maternal gestational weight gain was associated with increased neonatal sum of skinfolds and percentage body fat .…”
Section: Discussionsupporting
confidence: 92%
“…Very high maternal BMI (>35) has been associated with elevated systemic levels of inflammatory mediators, notably TNF and C-reactive protein (CRP) in the cord plasma. 81,82 In addition to these canonical inflammatory markers, maternal BMI is also a strong indicator of cord blood levels of malondialdehyde and NO, contributing to increased oxidative stress in the newborn. 83 In agreement with this hypothesis, transcriptional studies in cord blood have demonstrated elevated expression of genes involved in the cellular response to oxidative stress and inflammatory signaling with high maternal BMI, independent of offspring adiposity.…”
Section: Impact Of Maternal Obesity On Phenotypic and Functional Chanmentioning
confidence: 99%
“…Poor ex vivo monocyte responses in the offspring with pregravid obesity could potentially be tied to an altered inflammatory intrauterine environment. Very high maternal BMI (>35) has been associated with elevated systemic levels of inflammatory mediators, notably TNFα and C‐reactive protein (CRP) in the cord plasma . In addition to these canonical inflammatory markers, maternal BMI is also a strong indicator of cord blood levels of malondialdehyde and NO, contributing to increased oxidative stress in the newborn .…”
Section: Introductionmentioning
confidence: 99%
“…Each kg/ m 2 increase in pre-pregnancy BMI was associated with a −0.50% (95% CI, −0.83 to −0.17; p = 0.003) shorter cord blood TL and a −0.66% (95% CI, −1.06 to −0.25; p = 0.002) shorter placental TL [101]. Higher maternal pre-pregnancy BMI was also associated with increased newborn adiposity and inflammation [115]. Nonetheless, with adequate preventive measures maternal obesity could be reduced.…”
Section: Maternal Pre-pregnancy Bmimentioning
confidence: 94%